Nighttime chlorine monoxide observations by the Odin satellite and implications for the ClO/Cl2O2 equilibrium - Berthet, Gwenaël; Ricaud, Pierre; Lefèvre, Franck; Le Flochmoën, E.; Urban, Jakub; Barret, Brice; Lautie, N.; Dupuy, E.; De La Noe, J.; Murtagh, D. (Geophysical Research Letters, 2005)
We use measurements of chlorine monoxide (ClO) by the SMR instrument onboard the Odin satellite to study the nighttime thermal equilibrium between ClO and its dimer Cl2O2. Observations performed in the polar vortex during the 2002–2003 Arctic winter showed enhanced amounts of nighttime ClO over a wide range of stratospheric temperatures (185 < T < 225 K). Odin/SMR measurements are here compared to three-dimensional model calculations using various published estimations of the Keq equilibrium constant between ClO and Cl2O2. Our results show that the value of Keq currently recommended by JPL (Sander et al., 2003) leads to a large underestimation of the observed nighttime ClO amounts, and that a realistic estimation of Keq must lie between the values determined by Cox and Hayman (1988) and Von Hobe et al. (2005).